Assessing α-Bisabolol as a Transmucosal Permeation Enhancer of Buccal Local Anesthetics - Renê Oliveira do Couto; Douglas Vieira Thomaz; Maira Perez Ferreira Duarte; Renata Fonseca Vianna Lopez; Vinícius Pedrazzi; Osvaldo de Freitas; Gianluca Martino Tartaglia (MDPI AG, 2024)
Needle-free buccal anesthesia improves dental treatment outcomes for both patients and dentists. In this study, we report on an assessment of the enhancement effects of α-bisabolol on the in vitro transmucosal permeation of prilocaine hydrochloride (PCl) and lidocaine hydrochloride (LCl) from needleless buccal films. We also evaluated the mechanical properties of the film, which consisted of Methocel™ K100 LV as the film-forming polymer (3% m·m−1), PEG 400 as a cosolvent (15% m·m−1 based on drug loading), α-bisabolol (15 and 30% m·m−1 based on drug loading), and the drugs combined at a 1:1 ratio (15 mg·unit−1). The porcine esophageal epithelium was used as a membrane barrier, and artificial saliva was the release medium. After a 1 h experiment at 25 ± 2 °C, α-bisabolol significantly decreased, rather than enhanced, the permeation fluxes (five-fold), permeability coefficients (seven-fold), and retentions (two-fold) of both PCl and LCl through the epithelium, regardless of the concentration. Moreover, the resistance and flexibility of the films markedly decreased compared to those without α-bisabolol. Therefore, under the experimental conditions, using α-bisabolol as a buccal permeation enhancer for the hydrophilic local anesthetics PCl and LCl from buccal films is not feasible.